Research methods in human resource management - Anderson, Valerie (Chartered Institute of Personnel and Development, 2013)
Clear and easy to follow, this edition guides you through the planning and execution of HRM research projects, at any level. It is fully mapped to the CIPD advanced level module, Investigating a Business Issue and remains a key resource for anyone undertaking a research report